ANATOMI DAUN DAN TAKSONOMI SYZYGIUM ZIPPELIANUM MIQ., S. JAVANICUM MIQ. DAN S. RACEMOSUM (BL.) DC - Siti Sunarti (PTTI, 2007)
Leaf anatomy and taxonomy of Syzygium zippelinum Miq., S. javanicum Miq. and S. racemosum.